Два новых рода совок (Lepidoptera, Noctuidae) - Ключко, З.Ф. (Вестник зоологии, 1984)
Two New Noctuid Moth Genera (Lepidoptera, Noctuidae). Kljutshko Z. F.— Vestn. zool., 1984, No. 3. Desertoplusia gen. n. (type-species by original designation: Plusia bella Christoph, 1887) includes species: D. paghmana paghmana (Wiltshire, 1971), comb. n. and D. paghmana paupera (Wiltshire, 1971), comb. n. Pseudochalcia gen. n. (type-species by original designation and monotypy; Plusia inconspicua Graeser, 1892).